Non-invasive assessment by Doppler ultrasound of 155 patients with bioprosthetic valves: a comparison of the Wessex porcine, low profile Ionescu-Shiley, and Hancock pericardial bioprostheses. Issue 1 (July 1986) - Simpson, I A; Reece, I J; Houston, A B; Hutton, I; Wheatley, D J; Cobbe, S M
Abstract : One hundred and fifty five patients with 167 bioprosthetic valves (68 Wessex porcine, 54 Hancock pericardial, and 45 low profile Ionescu-Shiley pericardial valves) were studied by Doppler ultrasound. Valve gradients were calculated from the mitral and aortic flow velocities by the modified Bernoulli equation. Mean mitral gradients were significantly smaller across the Ionescu-Shiley valves than across the Wessex porcine or Hancock pericardial valves. Mitral pressure half time was, however, significantly longer in the Hancock pericardial than in the Wessex porcine or Ionescu-Shiley valves. No significant differences were seen among the groups of aortic bioprostheses, though the comparable size of Wessex porcine valves showed significantly higher gradients. Bioprosthetic regurgitation was detected in 13 of 103 mitral and 11 of 59 aortic valves, though it was suspected clinically in only 12 mitral and six aortic bioprostheses. Doppler ultrasound is a repeatable non-invasive method of acquiring haemodynamic information in vivo from a variety of bioprostheses and it can detect bioprosthetic regurgitation at an early stage.